(untitled) (Journal of Economic Research & Business Administration, 2016)
The top management of firm in modern market conditions has to involve in development of strategic decisions of analysts, otherwise, without carefully carried out strategic analysis, such decision can have casual character, to be not effective and is capable to result in the conditions of fierce competition in bankruptcy. The companies have to be able to give an assessment to the administrative activity if they intend to provide control of carrying out financial operations and to achieve performance of the organizational tasks facing them. Emergence of new methods of the analysis is an important source of increase of competitiveness of firm, helping it within uncertainty accurately to develop the main activities, to increase efficiency and to reduce risk of potential bankruptcy. The strategic analysis demands understanding from the guide of at what stage of development there is an enterprise before solving, where to move further. The effective information system providing with data for the analysis of last, real and future situations is for this purpose necessary.